Entre muros: os espaços dos condomínios residenciais fechados - Ferreira, Christiane Nicolau Rosendo (2012)
The cities as they grow, has been closed between new walls, leading to worsening of issues the streets and occupation of urban space, the privatization of public spaces, the neighborhood relationship mandatory, the allusion of greater security and status. With this, the public spaces of the contemporary city are marked by selective appropriation and differentiated spaces that should be accessible to everyone. The gated alters the relationship between public and private from the privatization of public spaces. In the southern city of João Pessoa, only in the neighborhood of the Sun Portal, has today closed with seven condominiums, each with its large leisure areas. How cities can generate a variety of uses with an extension of breakaway walls for those who owe more purchasing power? The objective of this research is to analyze the areas of collective use of closed condominiums: Cabo Branco Residence Prive, Puerta del Sol and Orchid Grove, the morphology and sociospatial organization, noting planning rules, forms, uses and user behaviors . The methodology of this research is structured using as reference base: Lynch (1997), Kohlsdorf (2005) and Gehl (2006). Despite the formal and functional similarities visible in these collective spaces, there are fundamental differences in the spatial practices of its users. Know them in order to understand the dynamics and performance of these spaces and the social logic of segregation and production part of contemporary culture.